The Scientific and Research Forces of Society and Their Development in the Regions - Bochko, Vladimir Stepanovich (Economy of Regions, 2019)
In the article I introduce the concept of “the scientific and research forces of society”. The concept characterises an independent factor of economic growth that includes a system of searching for new knowledge along with the mechanisms and structures for transferring it into production. I demonstrated the difference between the scientific and research forces of society and the scientific and intellectual potential of society. The general condition for the forces’ development is the establishment of the creative spirit in society, that is the positive attitude to search for new technological, economic and social ideas. The weak development of the society’s scientific and research forces is the reason for the restrained growth of the territories’ technological potential and the associated level of the population’s welfare. I analysed the dynamics of the number of personnel engaged in research and development. Further, I hypothesised that in Russia there has been a tendency for science to leave the region and concentrate in “capital territories”. That tendency leads to the possibility of the regional peripheral economy’s emergence. Thus, I substantiated the necessity of expanding the regional and urban research activities in order to form regional and urban scientific and research forces of society. Such forces will ensure the transition of the country, regions and municipalities to a new level of technological development. I proposed the measures for strengthening the relationship between science, government and business by creating a fiscal mechanism, reflecting the interests of entrepreneurs and society. The mechanism should include the creation of the fund for the development of science in Russia and its regions.